Pengaruh Media Audio Visual Terhadap Konsentrasi Belajar Anak Kelompok B Di Tk Pertiwi 2 Desa Ngarum, Kecamatan Ngrampal, Kabupaten Sragen Tahun Pelajaran 2016/2017 - Styoningsih, Hesti; , Dr. Darsinah, M. Si (2017)
The purpose of this study was to determine whether there is influence by the audio-visual media to the concentration of children's learning in kindergarten Pertiwi 2 Ngarum, Ngrampal, Sragen academic year 2016/2017. The subject of research is the first class group B consisted of 16 children. The technique of collecting data through observation, interviews and documentation. The results showed that one class group B hard to concentrating on delivering materials when the teacher in front of class, children often speak for themselves and stray from the topic being discussed. This is what shows that one class group B at TK Pertiwi 2 Ngarum, Ngrampal, Sragen shown that children concentrate less on the time of learning, after receiving treatment using Media Audio Visual children in group B at TK Pertiwi 2 Ngarum, Ngrampal, Sragen has increased in the case of concentrate, can pay attention to the teacher much longer than before. Keywords: Audio Visual Effect media, the concentration of children's learning